Efficacy and outcomes of ramucirumab and docetaxel in patients with metastatic non-small cell lung cancer after disease progression on immune checkpoint inhibitor therapy: Results of a monocentric, retrospective analysis - Kareff, Samuel A.; Gawri, Kunal; Khan, Khadeja; Kwon, Deukwoo; Rodriguez, Estelamari; Lopes, Gilberto de Lima; Dawar, Richa (Frontiers in Oncology, 2023)
Current first-line standard therapy for metastatic non-small cell lung cancer without driver mutations involves chemotherapy and immunotherapy combination. Prior to the advent of immune checkpoint inhibition, REVEL, a randomized phase III trial demonstrated improved progression-free and overall survival with ramucirumab and docetaxel (ram+doc) in patients who failed platinum-based first-line therapy. Long-term outcomes related to second-line ramucirumab and docetaxel after first-line immunotherapy exposure remain unknown. We analyzed outcomes for 35 patients from our center whom received ramucirumab and docetaxel following disease progression on chemotherapy and immunotherapy combination. Median progression-free survival among patients who received ram+doc after exposure to immunotherapy was 6.6 months (95% CI = 5.5 to 14.9 months; p<0.0001), and median overall survival was 20.9 months (95% CI = 13.4 months to infinity; p<0.0001). These outcomes suggest that there may a synergistic benefit to combining chemotherapy with anti-angiogenic therapy after immunotherapy exposure. Future analyses should be evaluated prospectively and among a larger patient subset.